Instant Reader Program: A Tool to Enhance Reading Skills Among Primary Pupils - Ruth Ortega-Dela Cruz; Mary Angela M. Ausa (JEE (Journal of English Education), 2025)
Early literacy remains a critical challenge in many public schools, particularly for non-readers in resource-limited settings, where effective remedial programs are scarce. This study assessed the effectiveness of the Instant Reader Program (IRP) in enhancing the reading skills of primary pupils at a public elementary school in the Philippines. Using a quasi-experimental one-group pretest-posttest design, 28 non-reading students participated in a 20-day structured intervention targeting phonemic awareness, word recognition, and sentence reading. Data were gathered through reading assessments, observation checklists, interviews, and teacher surveys. Quantitative results demonstrated significant improvements across all reading components, while qualitative data highlighted increased learner engagement and confidence. Despite challenges such as limited attention spans, insufficient materials, and minimal parental involvement, the findings validate the IRP as an effective remedial reading program for early learners. The study provides valuable insights for enhancing reading instruction and managing literacy initiatives in resource-limited public-school settings.